Virulence Factors and Antimicrobial Resistance in Pseudomonas Aeruginosa: A Review - Nawar Bahaa Abdulsahib; Al-Ruobayiee, Mahaba Razzaq; Shamsi, Zahraa Reda (American Journal of Biology and Natural Sciences, 2025)
Pseudomonas aeruginosa is a human microbe that infects individuals who have chronic pulmonary obstructive, cystic fibrosis (CF), wounds, burns, carcinoma, immunodeficiency, and serious infections that require ventilation, like covid-19. These bacteria are distinguished by types of resistance mechanisms, as well as significant virulence factors such as lipopolysaccharide, alginate, and phagocytosis-resistant capsules. These bacteria can also form biofilms, which are crucial in chronic infections because they are resistant to phagocytosis and elimination by the humoral and cellular immune systems. The fast development of P. aeruginosa resistance to almost all antibiotics makes this bacterium a major health interest; hence, it is crucial to investigate the virulence factors carried by bacteria and the antimicrobial mechanisms to identify appropriate solutions to lower or limit this resistance.